Extraction of pectin from different varieties of citrus Fruits and identify factors influencing extraction - طنجور, زنان (Latakia University Journal -Biological Sciences Series, 2020)
This study deals with the extraction of pectin from citrus fruit residues and the increase in the economic rents of citrus producers and manufacturers, because citrus peels are a by-product of their manufacture as a source of many economically important products in all industrial, food, health and environmental fields. The current work is devoted to the use and development of part of practical technology to extract value-added products, particularly pectin, from the peels of different types of citrus fruits, and apart from domestic consumption, there is a demand for pectin in the export and industrialization market, where the industry proves to be a good source of income and get rid of the problem Industrial to environmental pollution treatment. The aim of this study was to determine the optimal recovery conditions for pectin and then to evaluate these conditions by designing a extraction experiment using certain parameters such as citrus varieties (Shamouti orange, Valencia, navel, Baladi, Gripfruit) and the resulting pectin in take-over (15.62, 22.21, 24.81, 18.85, 26.80 %g dry substance), and optimum indicators of 90-95o° temperature, pH 2-2.2, alcohol concentration 95% of 150-200ml and recovery duration 1-2 hours.